Non-kin selection enhances complexity in cooperation: A unified quantitative law. (December 2022) - Wang, Xiaoliang; Harrison, Andrew
Abstract: How cooperation evolves in the presence of selfishness is a core problem in evolutionary biology. Selfish individuals tend to benefit themselves, which makes it harder to maintain cooperation between unrelated individuals and for living systems to evolve towards complex organizations. The general evolutionary model presented here identifies that non-kin selection is the root cause for cooperation between unrelated individuals and can enable and maintain higher complexity of biological organizations (the coexistence of more individuals of different types). The maintained number of genotypes within a cooperation organization is shown to follow a universal exponential law as a quantitative function of the population size and non-kin selection strength, showing a gene-pool-size invariance. Our results highlight that non-kin selection may be a hallmark of biological evolution, and play an important role in shaping life's potentials. Graphical Abstract: ga1 Highlights: Non-kin selection enhances complexity in a cooperation organization. The number of genotypes maintained in a cooperation organization follows a universal exponential law. The evolutionary model presented unifies cooperation between kin and non-kin.